Reliability of Xsens inertial measurement unit in measuring trunk accelerations: a sex-based differences study during incremental treadmill running - Miqueleiz, Unai; Aguado-Jimenez, Roberto; Lecumberri, Pablo; Garcia-Tabar, Ibai; Gorostiaga, Esteban M. (Frontiers in Sports and Active Living, 2024)
Inertial Measurement Units (IMUs) measure trunk-acceleration variables related to both running performances and rehabilitation purposes. This study examined both the reliability and sex-based differences of these variables during incremental treadmill running test. Eighteen endurance runners performed a test-retest on different days, and thirty runners (fifteen female) were recruited to analyse sex-based differences. Mediolateral (ML) and vertical (VT) trunk displacement and root mean square (RMS) accelerations were analysed at 9, 15, and 21 km•h -1 . No significant differences were found between test-retests [Effect size (ES)<0.50)]. Higher intraclass correlation coefficients (ICCs) were found in the trunk displacement (0.85-0.96) compared to the RMS-based variables (0.71-0.94). Male runners showed greater VT displacement (ES=0.90-1.0), while female runners displayed greater ML displacement, RMS ML and anteroposterior (AP), and resultant euclidean scalar (RES) (ES=0.83-1.9). The IMU was found reliable for the analysis of the studied trunk accelerationbased variables. This is the first study that reports different results concerning acceleration (RMS) and trunk displacement variables for a same axis in the analysis of sex-based differences.